Teacher’s Behaviors: Verbal and Non-Verbal Behavior During the English Classroom Interaction - Nova Linda; Mukhaiyar Mukhaiyar (International Journal of Educational Dynamics, 2020)
An effective teacher has to be able to create a good communication between the teacher and the students. It can be seen from teachers behaviour include verbal and non verbal behaviours. In teaching context, teachers convey interaction in the classroom to contribute to interpersonal attraction through teachers’ verbal and nonverbal behaviours. This research study explored the teachers’ behavior in English classroom interaction. This research design is a qualitative research. Participants were two teachers at English School Indonesia, who taught in two intermediate levels. One teacher was represented for each classroom. The instruments used to collect the data was observation and interview. During the observation, each teacher was observed using video recording. And then the teachers were interviewed to strengthen the result of observation. The research found that both teachers who teach intermediate levels had effective behaviors during the English classroom interaction. The students were motivated to learn English